Development of Anti-Bacterial and Anti-Viral Nonwoven Surgical Masks for Medical Applications - Mazyar Ahrari; Mehmet Karahan; Muzzamal Hussain; Yasir Nawab; Asfandyar Khan; Amir Abbas Shirazi (Tekstilec, 2022)
This article aims to investigate the development of surgical masks for medical applications by incorporating biocidal silver nanoparticles. Medical masks were developed in three layers of a nonwoven fabric, where the outer and inner layers were made of a spun-bond polypropylene nonwoven fabric and the middle layer consisted of a melt-blown nonwoven polypropylene fabric. In this study, silver nanoparticles in the concentrations of 1–5% were applied to masks with the pad-dry-cure method. The samples were cured at room temperature and subsequently examined for antimicrobial properties. Scanning electron microscopy, energy dispersive spectroscopy and Fourier transform infrared spectroscopy were used to investigate the morphological characteristics and chemical composition of the samples. Microbial cleanliness, bacterial filtration efficiency, antiviral effect and breathability tests were performed according to standard test protocols. The results revealed that the application of silver nanoparticles to a three-layer mask rendered the end product with outstanding antimicrobial and antiviral properties with poor breathability (air permeability) results.